2017
DOI: 10.1007/s10753-017-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Fat Diet on Adipose Tissue CD8+ T Cells in Young vs. Adult Mice

Abstract: T cells are involved in chronic inflammation of adipose tissue in obese conditions. However, the impact of age on the adipose T cells remains unknown. In this study, we investigated T cells in the white adipose tissue of young and adult mice. Obesity was induced in the mice using a high-fat diet (HFD) for 14 weeks. The young mice were fed an HFD at 3 weeks old, and adult mice were fed the HFD at 12 weeks old. Relative to adult mice, the young mice gained less fat and exhibited better glucose tolerance. Their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The primary function of CD8 + T cells, also known as cytotoxic T cells, is to kill infected cells by producing perforin, granzymes and inflammatory cytokines, namely IFN-γ (reviewed in [ 251 ]). The degree of splenic CD8 + T cell activation in vitro was demonstrated to be markedly increased when co-cultured with obese versus lean AT [ 22 ], which complements in vivo reports in humans and rodents wherein the proportion of activated CD8 + T cells is increased in the SVF of obese AT versus lean [ 22 , 23 , 24 , 25 , 50 , 196 , 198 , 252 ].…”
Section: Obese Adipose Tissue Immune Cells and Modulation By mentioning
confidence: 69%
“…The primary function of CD8 + T cells, also known as cytotoxic T cells, is to kill infected cells by producing perforin, granzymes and inflammatory cytokines, namely IFN-γ (reviewed in [ 251 ]). The degree of splenic CD8 + T cell activation in vitro was demonstrated to be markedly increased when co-cultured with obese versus lean AT [ 22 ], which complements in vivo reports in humans and rodents wherein the proportion of activated CD8 + T cells is increased in the SVF of obese AT versus lean [ 22 , 23 , 24 , 25 , 50 , 196 , 198 , 252 ].…”
Section: Obese Adipose Tissue Immune Cells and Modulation By mentioning
confidence: 69%
“…The presence of saturated fat in HC diet allows for the potential association of adipose inflammatory pathways with the observed deleterious effects. Studies showed inflammatory changes in adipose tissue in response to high-fat feeding [ 45 , 47 , 71 ]. Indeed, in the present study, an increased expression of IL1- β and TNF- α was observed in adipose tissue of HC-fed rats consistent with prior research [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…NASH) being heavily reported. The age at which one starts inducing obesity can also have a profound effect on results, with one study reporting significant changes in the immune phenotype of mice started on a high fat diet at 3 weeks of age that was lost if mice were instead started on the same diet at 12 weeks of age [30]. Intriguingly, caloric restriction has been found to reverse some of the effects of the accelerated immune aging seen in obesity, with reports of delays in T cell senescence compared to ad libitum fed control mice and non-human primates [14,15,31].…”
Section: Effects Of Obesity On the Immune Systemmentioning
confidence: 99%
“…Differences in the model and experimental design could account for these discrepancies. As mentioned before, the length of time on the diet and when the diet was started could have a profound impact on the extent of obesity’s effect on T cells [30]. …”
Section: Obesity and T Cell Exhaustionmentioning
confidence: 99%